(untitled) (Proceedings of the International Conference on Education, 2025)
This study transforms mathematics education in indigenous communities by integrating ethnomathematics with modern teaching approaches. In this context, ethnomathematics connects mathematical concepts with Dayak culture, specifically through the Floating House (Huma Lanting), which reflects a local understanding of numeracy. The aim is to make mathematics learning more relevant to students’ needs and easier for them to comprehend. Ethnomathematics links mathematical concepts with local cultural practices and indigenous knowledge, which can foster a deeper understanding of mathematics. However, the complexity of combining traditional knowledge with formal mathematics may increase the cognitive load on students, potentially hindering their learning process. This research employs a mixed-method approach to identify key strategies for effectively integrating ethnomathematics and reducing cognitive load. The methods used include the Worked Example, which provides concrete examples to ease comprehension difficulties; the Split-Attention Effect, which minimizes distractions by visually integrating information; and the Modality Effect, which uses a combination of visual and auditory modalities to enhance learning efficiency. The approach takes quantitative research, involving learning outcome tests, cognitive load assessments, and in-depth interviews. The research sample consists of 144 students who provide data for an in-depth analysis of the effectiveness of the applied strategies. The study’s findings show that targeted teaching techniques can significantly reduce cognitive load, allowing students to engage more deeply with mathematical concepts and improve overall learning outcomes.